Embracing complex adaptive practice: the potential of lesson study. Issue 2 (27th May 2021) - McMillan, Paul; Jess, Mike
ABSTRACT: The current neoliberal political climate in education has narrowed the focus of teachers' professional development and reduced their work in the classroom to a simple and predictable process. In this article, we challenge this view by deploying a range of complexity thinking concepts to present an account of teachers as self-organising, inquiring, and emergent professionals, whose classroom practice is constantly evolving as they negotiate different boundaries and make connections across the nested layers of the education system. Lesson Study is recognised as a collaborative, school-based, and long-term form of professional development that appears to have the potential to foster these complex and adaptive features of classroom practice. To this end, in the closing stages of this article, we present examples from our involvement in two longitudinal research projects in Scotland. The project leaders have set up appropriate contexts for Lesson Study that are ripe for a focus on complex adaptive practice in the future. We share our next steps in these two projects but remain realistic about the implications of developing complex adaptive practice through Lesson Study in the current political climate.